Proceedings of the 1st International Workshop on Computational Approaches to Historical Language Change 2019
DOI: 10.18653/v1/w19-4713
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Historical Phonetic Features using Deep Neural Networks: A Case Study of the Phonetic System of Proto-Indo-European

Abstract: Traditional historical linguistics lacks the possibility to empirically assess its assumptions regarding the phonetic systems of past languages and language stages beyond traditional methods such as comparative tools to gain insights into phonetic features of sounds in proto-or ancestor languages. The paper at hand presents a computational method based on deep neural networks to predict phonetic features of historical sounds where the exact quality is unknown and to test the overall coherence of reconstructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Since the probability of this being a random outlier is relatively low given that the clade is strongly supported by the data, this clustering might be an indication that *m phonotactically differs from other sonorants. An inconsistency within the pie nasal series was already detected in Hartmann (2019). Although this is an accidental finding, it ties in with recent discussions on the sonority of pie */m/ in the context of the pie sonority hierarchy.8…”
Section: Local Predictability and Statistical Constraint Effects In Piesupporting
confidence: 62%
“…Since the probability of this being a random outlier is relatively low given that the clade is strongly supported by the data, this clustering might be an indication that *m phonotactically differs from other sonorants. An inconsistency within the pie nasal series was already detected in Hartmann (2019). Although this is an accidental finding, it ties in with recent discussions on the sonority of pie */m/ in the context of the pie sonority hierarchy.8…”
Section: Local Predictability and Statistical Constraint Effects In Piesupporting
confidence: 62%
“…We are also not the first researchers to explore neural modeling of phonetic features. Hartmann (2019Hartmann ( , 2021 showed that neural networks can predict features of Proto-Indo-European phones given the features of a trigram context, which reflect SYN-CHRONIC (applying at a particular stage in a language's history) phonetic phenomena. Our neural network, on the other hand, predicts the probability of feature changes in a sound change, given DI-ACHRONIC data (data that represents change over time).…”
Section: Related Workmentioning
confidence: 99%
“…Phoneme classification for Bengali Language using DPFs and deep neural network was reported in [21]. In [22], a deep neural network is used to predict historical phonetic features drawn upon synchronic phonetic patterns arising from coarticulation and statistical constraints in Proto-Indo-European language. In [23], extracted acoustic features of speech signal using hamming window and pre-emphasis filter, in addition to extracted decompositional features using daubechies-filtered 5th-depth Wavelet Packet Decomposition (WPT), are optimized using genetic algorithm to classify Turkish vowels.…”
Section: B Literature Reviewmentioning
confidence: 99%